Microbiota-induced type I interferons instruct a poised basal state of dendritic cells - Schaupp, Laura; Muth, Sabine; Rogell, Leif; Kofoed-Branzk, Michael; Melchior, Felix; Lienenklaus, Stefan; Ganal-Vonarburg, Stephanie C.; Klein, Matthias; Guendel, Fabian; Hain, Tobias; Schütze, Kristian; Grundmann, Ulrike; et al. (Cell, 2020)
Environmental signals shape host physiology and fitness. Microbiota-derived cues are required to program conventional dendritic cells (cDCs) during the steady state so that they can promptly respond and initiate adaptive immune responses when encountering pathogens. However, the molecular underpinnings of microbiota-guided instructive programs are not well understood. Here, we report that the indigenous microbiota controls constitutive production of type I interferons (IFN-I) by plasmacytoid DCs. Using genome-wide analysis of transcriptional and epigenetic regulomes of cDCs from germ-free and IFN-I receptor (IFNAR)-deficient mice, we found that tonic IFNAR signaling instructs a specific epigenomic and metabolic basal state that poises cDCs for future pathogen combat. However, such beneficial biological function comes with a trade-off. Instructed cDCs can prime T cell responses against harmless peripheral antigens when removing roadblocks of peripheral tolerance. Our data provide fresh insights into the evolutionary trade-offs that come with successful adaptation of vertebrates to their microbial environment.